2020
DOI: 10.3389/fvets.2020.00321
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA Integrity and Male Fertility in Farm Animals: A Review

Abstract: The accurate prediction of male fertility is of major economic importance in the animal breeding industry. However, the results of conventional semen analysis do not always correlate with field fertility outcomes. There is evidence to indicate that mammalian fertilization and subsequent embryo development depend, in part, on the inherent integrity of the sperm DNA. Understanding the complex packaging of mammalian sperm chromatin and assessment of DNA integrity could potentially provide a benchmark in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 182 publications
(161 reference statements)
1
54
1
1
Order By: Relevance
“…The GWAS has been previously used to aid the identification of genetic variants underlying reduced male reproductive performance as well as of candidate genes for semen traits in human [ 22 , 30 ], livestock [ 30 , 31 ], as well as in more suitable animal models, as pigs [ 14 , 15 ]. In either case, the rationale behind was to improve the identification of males suffering from idiophatic sub/infertility, despite providing ejaculates with values considered “within normal limits” [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GWAS has been previously used to aid the identification of genetic variants underlying reduced male reproductive performance as well as of candidate genes for semen traits in human [ 22 , 30 ], livestock [ 30 , 31 ], as well as in more suitable animal models, as pigs [ 14 , 15 ]. In either case, the rationale behind was to improve the identification of males suffering from idiophatic sub/infertility, despite providing ejaculates with values considered “within normal limits” [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This unexplained subfertility had led to calls over the years for more sophisticated semen analyses, aiding elimination of clearly subfertile sires [ 12 ]. Considering that the spermatozoa carries intact, healthy attributes that could define fertility when retrospectively related to the observed sire fertility [ 12 ], novel methods include omics of spermatozoa [ 13 , 14 , 15 ] and seminal plasma (SP, [ 7 ]), which is a trend also used in human andrology [ 16 ]. However, reliable prognosis for fertility in either species has remained elusive, often because the definition of fertility levels for a given male must indeed consider a plethora of confounding factors, including number of inseminated spermatozoa, intercourse frequency and, in pigs, an even number of females undergoing AI, number of AIs per oestrus, seasonality, the systems used to detect oestrus, farm characteristics, AI procedures, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The main task of the sperm cell is to deliver the paternal genome to an oocyte during fertilization. Sperm DNA integrity is crucial for successful fertilization and subsequent embryo development (Kumaresan et al, 2020). The sperm cell has a unique chromatin structure where most of the histones are replaced by smaller proteins, called protamines, during spermatogenesis (Champroux et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In artificial breeding, it is well-understood that sperm must possess some functionalities for successful fertilization of oocyte, which include, but not restricted to, motility to reach the site of fertilization ( 42 ) functional membrane integrity to establish sperm–oviduct reservoir ( 4 , 5 , 43 ) and sperm–oocyte binding ( 44 ) and intact non-reacted acrosome for sperm penetration into the oocyte ( 5 ). Additionally, it has been reported that sperm DNA integrity ( 45 ) and status of lipid peroxidation ( 4 , 46 ) are also related to male fertility. In the present study, we observed that sperm motility, membrane, and acrosomal integrity were significantly higher, while the status of protamination and lipid peroxidation were significantly lower in high- compared to low-fertile buffalo bulls.…”
Section: Discussionmentioning
confidence: 99%